Reliability testing of the balance error scoring system in children between the ages of 5 and 14 - Hansen, C.; Cushman, D.; Chen, W.; Bounsanga, J.; Hung, M. (Clinical Journal of Sport Medicine, 2017)
Objective: Pediatric concussion is an extensive public health concern with a complex clinical presentation. Balance assessment has been well-studied in the adult population, but has been limited in children. We aimed to assess the reliability and minimum detectable change (MDC) of the Balance Error Scoring System (BESS) in healthy children.